Utilization of the Homo Wajakensis Site and Regional Museum Tulungagung as a History Learning Media - Lazuardi, Deris; Santoso, Budi; Putranto, Anggoro (Universitas Negeri Semarang, 2023)
The Homo Wajakensis Site and Tulungagung Regional Museum are historical sites and historical museums that can be used to study the preliterate or prehistoric period. Many sources say that Homo Wajakensis was found in the Boyolangu District, Tulungagung Regency. This is wrong because from research that researchers can or obtain is that Homo Wajakensis was found in Gamping Village, Campurdarat District, Tulungagung Regency. The aims of this research are (1) to find out in depth about the homo wajakensis site and the Tulungagung regional museum; (2) for the use of the Homo Wajakensis site and the Tulungagung regional museum as a history learning medium for students; (3) for teachers' best practices in teaching history in schools; (4) for student responses in learning history by utilizing the Homo Wajakensis site and the Tulungagung regional museum. The results of this research are (1) the researcher knows in depth about the homo wajakensis site and the Tulungagung regional museum, especially the truth about where it was found; (2) the homo wajakensis site and the Tulungagung regional museum as a medium for learning history for students are the best solution in increasing student motivation; (3) sites and museums are the best learning media for teacher practice in teaching history in schools; (4) students, especially students at SMA Kauman (a Senior High School) class X and also SMP Srengat (a Junior High School) class VII, seem more interested in practical learning or seeing objects directly historical objects at the Homo Wajakensis site and the Tulungagung Regional Museum.